Implementasi Model SMCR dalam Stretegi Komunikasi Layanan Publik di KOMINFO Kota Medan - Hanafi, Muhammad Reza; Kholil, Syukur (Penerbit Goodwood, 2024)
Purpose: This study aims to evaluate and explore the application of the SMCR Model (Source, Message, Channel, Receiver) in public service communication strategies at the Department of Communication and Information (Kominfo) in Medan City, with particular emphasis on exploring patterns of communication effectiveness and public engagement. Methodology: The method used is a case study with data collection through interviews, observation, and documentation. The analysis is based on the SMCR components, including source, message, channel, and receiver. Results: The results show that the credibility of the information source, message clarity, and the use of diverse communication channels play significant roles in the effectiveness of public communication. However, challenges related to the digital divide still hinder information access for certain segments of society. Strategic implementation steps have been identified, including: establishing a multi-channel communication framework, developing capacity building programs for communication staff, implementing regular channel effectiveness monitoring systems, and creating targeted outreach programs for digitally underserved communities. Limitations: The limitation of this research lies in its limited regional scope and focus on a single institution, which may affect the generalizability of the findings. Contribution: The contribution of this study is providing practical recommendations for public institutions to develop more inclusive communication strategies, especially in addressing the digital divide through channel diversification and improving staff capacity.